Drivers of farmers’ adoption of hermetic storage bags in Ghana - Namah Taku-Forchu; Misty D Lambert; Michael S. Retallick; Jonathan D Ulmer; George P Opit (Journal of International Agricultural and Extension Education, 2023)
Post-harvest loss is a global challenge due to its serious threat to food security. Hermetic storage bags offer one way to combat the loss of food after harvest. The rate at which farmers adopt hermetic bags largely depends upon their access to information and training about the technology. The adoption of hermetic storage bags in Dormaa, Ghana, was the focus of this quantitative cross-sectional research study. This study sought to describe maize farmers’ perceptions of the hermetic storage bags in Dormaa, Ghana, based on the perceived innovation attributes and to ascertain farmers’ stages of adoption of the hermetic storage bags using Rogers’s (2003) innovation-decision model. A multistage systematic sampling technique was used to survey 217 maize farmers in four communities where maize production was the main economic activity. Data indicated that the largest group of farmers were at the confirmation stage of Rogers’ model. The logistic regression model was used to ascertain the influence of the innovation attributes on adoption. The findings reveal that of the five innovation characteristics, relative advantage, compatibility, and complexity are the key and significant drivers of the adoption of hermetic storage bags, with relative advantage and compatibility increasing the adoption likelihood and complexity reducing it. The study, therefore, recommends that communities lagging behind others in adoption should be targeted for additional training.
Keywords: post-harvest loss; hermetic bags; extension; diffusion of innovation